Influence of electrohydrodynamics on the drying characteristics, microstructure and volatile composition of apricot abalone mushroom (Pleurotus eryngii) - Peng Guan; Changjiang Ding; Jingli Lu; Wurile Bai; Jiaqi Liu; Junjun Lian; Zhiqing Song; Hao Chen; Yun Jia (Current Research in Food Science)
The study explored the use of current fluid dynamics drying technology for apricot abalone mushroom, examining how different output voltages (15, 25, and 35 kV) affected drying characteristics, microstructure, and volatile components. Comparisons were made with samples dried using hot air drying (HAD) and natural air drying (AD). Results revealed that HAD had the fastest drying rate at 0.29664(g·h−1). However, apricot abalone mushroom treated with electrohydrodynamic drying (EHD) maintained a color closer to fresh samples, exhibited a 21% increase in the ordered structure of protein secondary structure, a 12.5-fold increase in bound water content, and the most stable cell structure compared to HAD and AD treatments. A total of 83 volatile organic compounds were identified in the apricot abalone mushroom, with alcohols and aldehydes being the most prominent in terms of threshold and relative content, peaking in the 35 kV treatment group. These findings provide both experimental and theoretical insights into applying current fluid dynamics for drying apricot abalone mushroom.